2011
DOI: 10.1246/bcsj.20110178
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Visualization of Right- and Left-Handed Helical Alignments of DNA in Chiral Vortex Flows

Abstract: In a vortex generated by mechanical rotary stirring in an optical cell, DNA molecules in pure water temporarily align helically to the spiral flow, and dynamically display strong induced circular dichroism (CD) and linear dichroism (LD) responses. Although a sample solution without stirring provided the characteristic CD spectral pattern of DNA, an entirely different macroscopic CD spectral pattern with a much larger intensity and LD spectrum appeared upon mechanical rotary stirring of the sample solution. Clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…These differences in activity depending on the chirality of biomolecules are related to the origin of life on Earth and are one of the most attractive mysteries in the life sciences. A number of reports have proposed1 mechanisms of homochirality, such as those for circularly polarised light23, magneto-chiral fields4, vortex and stirring conditions56789, and nonlinear autocatalysis101112. However, a final conclusion regarding a universal homochirality mechanism has not yet been reached.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These differences in activity depending on the chirality of biomolecules are related to the origin of life on Earth and are one of the most attractive mysteries in the life sciences. A number of reports have proposed1 mechanisms of homochirality, such as those for circularly polarised light23, magneto-chiral fields4, vortex and stirring conditions56789, and nonlinear autocatalysis101112. However, a final conclusion regarding a universal homochirality mechanism has not yet been reached.…”
mentioning
confidence: 99%
“…demonstrated the chiral sign induction in the aggregation of achiral porphyrins in aqueous solutions through vortices. Tsujimoto et al 9. reported that DNA molecules could align helically in a vortex generated by mechanical stirring.…”
mentioning
confidence: 99%
“…In this review article, I have summarized and extended our findings presented in references [13,19,20]. Small molecules do not orient in response to macroscopic fluid flows of solvent molecules, because Brownian motions are dominant over hydrodynamic interactions at the molecular level.…”
Section: Discussionmentioning
confidence: 82%
“…Next, a one-handedly twisted supramolecular nanofiber was found to show unequal LD responses in right-and left-handed vortex flows, owing to unequal helical alignment of the nanofiber [19]. Such phenomena were observed not only in the artificial helical supramolecular nanofibers but also in biological nanofibers such as double-stranded DNA [20].…”
Section: Open Accessmentioning
confidence: 93%
See 1 more Smart Citation